2016
DOI: 10.7146/aul.154.126
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Climate and Student Achievement: Evidence from Schools and Classrooms

Abstract: Abstract:Disciplinary climate has emerged as one of the single most important factors related to student achievement. Using data from the OECD Programme for International Student Assessment (PISA) 2003 for Canada, Denmark, Finland, Iceland, Latvia and Norway we find a significant and nontrivial association between the perceived disciplinary climate in the classroom and students' mathematics performance in Canada, Denmark and Norway. Furthermore we exploit country specific class-size rules in order to single ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…This is consistent with the results reported by previous research (e.g. Arum & Velez, 2012;Ning et al, 2015;Sortkaer & Reimer, 2016;Usta, 2014). It cannot be expected that student achievement is independent of the characteristics of the classroom environment.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the results reported by previous research (e.g. Arum & Velez, 2012;Ning et al, 2015;Sortkaer & Reimer, 2016;Usta, 2014). It cannot be expected that student achievement is independent of the characteristics of the classroom environment.…”
Section: Discussionsupporting
confidence: 94%
“…Studies of the relationship of these variables to mathematical achievement showed that a positive, nondisordered classroom environment improves mathematics achievement for students (e.g. Akyüz & Satıcı 2013;İlgün-Dibek, 2015;Sortkaer & Reimer, 2016;Usta, 2014). Tennant and colleagues (2015) suggested that students tend to have better math achievement when teachers focus on helping and guiding them in understanding mathematical concepts and solving questions.…”
Section: Introductionmentioning
confidence: 99%
“…no que se refere à socialização as representações e as crenças são tão importantes quanto os fatos ou, mais precisamente, que elas são fatos simbólicos dotados de uma eficácia própria". Ademais, metodologicamente, além de viável, essa estratégia tem se mostrado eficaz e apropriada à investigação de fenômenos educacionais, especialmente de fenômenos interativos em sala de aula, conforme indica a literatura (Matos, 2006;Sortkaer & Reimer, 2016).…”
Section: Indiscipline Scolaire • Différence De Genre • Enseignement P...unclassified
“…For instance, Reynolds et al ( 2017 ) suggested that school climate and school identification (connectedness, belonging, relatedness) are conceptualized as distinct but related concepts and should be investigated in the same model to explain academic development. Speaking of the school environment, one of the key environmental elements is the disciplinary climate (Cheema and Kitsantas, 2014 , 2016 ; Sortkær and Reimer, 2016 ; Chi et al, 2018 ), which refers to the degree to which noise and disorder are suppressed, teachers have more time to cover the curriculum and use diverse teaching strategies, and students have time and opportunities to concentrate on academic tasks (Cheema and Kitsantas, 2014 , 2016 ). And existing findings have revealed the moderating effect of disciplinary climate on the relationships between other variables and academic outcomes, such as mathematics performance (Sortkær and Reimer, 2016 ) and science achievement (Chi et al, 2018 ), but no similar exploration has been done in the reading context.…”
Section: Introductionmentioning
confidence: 99%